How Attitude, Perceived Savings, Price Discount Affect, Perceived Food Quality Shapes Purchase Intentions Of Menu Rahmah - Wan Rasyidah Wan Nawang; Amirul Amri Zainudin; Nor Haziah Hashim (UiTM Press, Universiti Teknologi MARA, 2026)
Tier 3- Indexed by MyCite